THE STEREOCHEMISTRY EFFECT OF EUGENOL, CIS-ISOEUGENOL AND TRANS-ISOEUGENOL ON THEIR CATALYTIC HIDROGENATION - M. Muchalal (Universitas Gadjah Mada, 2004)
The stereochemistry effect of eugenol, cis-isoeugenol and trans-isoeugenol on their catalytic hydrogenation by Ni/g-Al2O3 catalyst was investigated. In this investigation, the catalyst is prepared by impregnation of Nickel into solid of γ-Al2O3 in methanol as a solvent. The calcination process, which is followed by reduction, is performed on Muchalal reactor at 400 oC. After that, the catalytic hydrogenation is carried out under hydrogen gas atmosphere by mixing 10 mL sample and 0.5 g Ni/g-Al2O3 catalyst at 200 oC for 3 hours. The stereochemistry effect of reactants is evaluated by computer modelling using PM3 semiempirical methods. The mass spectrum of catalytic hydrogenation product from those compounds shows a molecular ion at m/z 164, which proves the existence of 2 -methoxy-4-propylphenol. The eugenol gives the highest conversion (99%), followed by cis-isoeugenol (81%) and trans-isoeugenol (67%). It was found that there is a correlation between the stereochemistry of those compounds and catalytic reactivity.